Implementasi Pengembangan Kurikulum Kitab Kuning di Madrasah Aliyah Negeri Program Keagamaan (Manpk) Man 2 Samarinda (Studi Pada Manpk Man 2 Samarinda) - Wahyudi, Wahyudi; Jannah, Fathul; Tamam, Badrut (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 2 (2024)DO - 10.24843/PJIIB.2024.v24.i02.p05, 2024)
The significance of the approach in learning the yellow book—an Arabic book without syakal or harakat that Middle Eastern academics wrote in the Middle Ages and contained Islamic religious sciences—motivates this study. The appropriate approach must be taken when studying the yellow book in order to effectively communicate the learning objectives. In addition to the Al-Qur'an and As-Sunnah, the yellow book is typically studied in Islamic boarding schools and serves as the primary teaching resource. The yellow book is nevertheless studied in formal institutions as well, notably MANPK MAN 2 Samarinda, in addition to Islamic boarding schools. By taking part in numerous competitions related to the program to improve the yellow book, MANPK MAN 2 Samarinda pupils are able to read and comprehend the yellow book.